Fiscal transfers and economic convergence: Evidence from China. (15th March 2022) - Liu, Guanchun; Song, Jianbo; Zhang, Chengsi
Abstract: This study investigates how fiscal transfers affect economic convergence across Chinese provinces. Using the data of 26 provinces over 1995–2016, we find that fiscal transfers promote an 'immiserising convergence' resulting from a decline in growth in rich provinces. Specifically, general fiscal transfers play an insignificant role, and special fiscal transfers facilitate the economic growth of poor provinces but impede that of rich provinces. Furthermore, the mechanism tests show that the positive effect of fiscal transfers on productive expenditures declines with higher initial real GDP per capita and becomes negative in rich provinces. To further identify causality, we conduct a difference‐in‐differences estimate by exploiting the Great Western Development Programme as a quasi‐natural experiment and employ an instrumental variable approach with ethnic diversity in 1990 as the instrument. In sum, our findings suggest that the positive growth effect of fiscal transfers in poor provinces is at the cost of sluggish growth in rich provinces.